The Current Status of Arabic Language Teaching in Nigeria: Challenges and Developments: SECOND LANGUAGE TEACHING - Khalil Mohammad Usman Gbodofu (Al-Ḍād Journal, 2022)
We discuss in this paper the teaching of the Arabic Language in Nigeria in the 21st century, considering the challenges that face this language and the developments it gains from its lovers and scholars in this country. Therefore, we started by narrating the history of Nigeria and emergence of Arabic Language therein, as we mentioned the means through which it arose in the country. We discussed the role of the colonialists in the weakness of the standard of Arabic Language and the contribution of some Arabic scholars in translating many English texts into Arabic. We also investigated the conditions of Arabic education in Nigerian universities and into the benefits for some students of Arabic Language with modern technological education. Keywords: Status, Education, Challenges, Developments, Nigeria